Luxúria e iconografia na escultura românica portuguesa - Joaquim Luís Costa (Medievalista)
The luxury on the Portuguese Romanesque iconography – as a synonym of eroticism –, has been little studied. The present article contributes to this debate by analyzing different symbolic and thematic areas that can be found on the Medieval Bestiary, on the Bible, on the human being and on the animal world representations. The investigation led us to the conclusion that the luxury can be found from the north to the south of the country, though more incident on the north, and especially focused on the mermaid theme. In this respect, the Travanca Monastery works as an irradiating center presenting sexual representations somehow repressed.